PENDEKATAN SAINTIFIK: MELIHAT ARAH PEMBANGUNAN KARAKTER DAN PERADABAN BANGSA INDONESIA - Wedra Aprison & Junaidi (IAIN Tulungagung, 2017)
Indonesia’s current education emphasizes the scientific approach, from elementary school, junior high school and college. It is clearly visible in the curriculum documents applied by the current government of Indonesia which is known as the 2013 Curriculum. By conducting philosophical studies, a scientific approach that emphasizes rationality can be a knife to seek and solve the causes of events in science. In Marx’s terms, science and technology infrastructures, both of which will determine the superstructure of the international world including culture, morals, law, and even religion. Science can also eliminate unfounded (magical) trust in traditional societies. In the context of Indonesia scientific approach to form a nation-based character rational science.In other words, the more dominant the critical scientific awareness than the mystic. According to Agus Comte and more clearly on Freire, divides human consciousness into three levels: magical awareness, native awareness, and critical awareness. The civilization of the Indonesian nation seems to be in a great deal of this magical awareness. With a scientific approach, it is not impossible for Indonesian civilization to move to the level of critical awareness. Critical awareness is an asset to a more civilized civilization in the future.